On the Possibility of Creating Humidity Sensors for Agriculture Based on Silicon-Germanium - Sapaev Bayramdurdy; Sapaev Ibrohim Bayramdurdievich; Khakimov Dilshod Solihjon o’g’li; Sadikova Nargiza Baxtiyarovna (Zien Journals, 2022)
This paper shows the possibility of creating a new type of sensor - semiconductor humidity sensors using silicon-germanium solid solutions. It has been proven that it is possible to create humidity sensors based on Si1-xGex solid solutions in the form of a Schottky barrier with a wide range of sensitivity to the relative humidity of the environment.
Keywords: Soil moisture meters; laboratory methods; soil moisture